2018
DOI: 10.1007/s10750-018-3672-2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects on organic matter processing from soils to the ocean: are priming effects relevant in aquatic ecosystems?

Abstract: Organic matter (OM) is degraded during transport from soils to oceans. However, there are spatial and temporal variabilities along the aquatic continuum, which hamper the development of carbon cycling models. One concept that has been applied in this context is the priming effect (PE), describing nonadditive effects on OM degradation after mixing sources of contrasting bioavailability. Studies on the aquatic PE report divergent results from positive (increased OM degradation rates) to neutral, to negative (dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(130 citation statements)
references
References 99 publications
6
124
0
Order By: Relevance
“…Our observations of negative priming point to several unanticipated effects of algal‐mediated labile C addition on recalcitrant C degradation in aquatic ecosystems. Foremost, our study reiterates the question of why negative priming occurs in some settings, whereas positive priming occurs in others (Bengtsson et al, ). In two previous litter decomposition studies, increased algal biomass under high nutrients erased positive algal‐induced priming (Danger et al, ; Halvorson et al, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our observations of negative priming point to several unanticipated effects of algal‐mediated labile C addition on recalcitrant C degradation in aquatic ecosystems. Foremost, our study reiterates the question of why negative priming occurs in some settings, whereas positive priming occurs in others (Bengtsson et al, ). In two previous litter decomposition studies, increased algal biomass under high nutrients erased positive algal‐induced priming (Danger et al, ; Halvorson et al, ).…”
Section: Discussionsupporting
confidence: 78%
“…Though likely important for the global C cycle, priming effects and their mechanisms remain poorly studied in aquatic systems (Bengtsson, Attermeyer, & Catalán, 2018;Cole et al, 2007;Guenet et al, 2010). Some studies have reported positive priming (increased decomposition rate) with additions of labile glucose, leachates or algal exudates on breakdown of recalcitrant dissolved or particulate C (Bianchi et al, 2015;Danger et al, 2013;Hotchkiss, Hall, Baker, Rosi-Marshall, & Tank, 2014), whereas others have reported no or negative priming (decreased decomposition rates ;Bengtsson et al, 2015;Catalán, Kellerman, Peter, Carmona, & Tranvik, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While we did not calculate the magnitude of priming effects, our observation of a marginally significant increase in nonalgal DOM decomposition is consistent with the average positive priming effect of 12.6% found across all aquatic priming studies, which was not statistically different than zero (Bengtsson et al ). High positive priming effects have been observed in some freshwater experiments, with vascular plant leachates decomposing 2–74 times more rapidly in the presence of priming substrates (Bianchi et al ; Ward et al ), but other experiments have shown zero to negative priming effects in different environments such as lakes, the hyporheic zone, and marine sediments (Gontikaki et al ; Bengtsson et al ; Catalán et al ), illustrating the diversity in microbial responses to multiple substrates across environments.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, the addition of labile DOM did not stimulate the bacterial degradation of riverine DOM in marine coastal environments (Blanchet et al 2017), neither hyporheic DOM in rivers (Bengtsson et al 2014) nor lacustrine DOM (Catalán et al 2015). According to a recent meta-analysis on the occurrence of PE in aquatic ecosystems, the concept relies on assumptions that may limit its incorporation into our understanding of C cycling in aquatic ecosystems (Bengtsson et al 2018). Indeed, the basic approach for investigating the occurrence of PE consists in adding simple and labile organic molecules into a ambient sample containing the recalcitrant DOM pool.…”
Section: * Thibault Lambertmentioning
confidence: 99%
“…Indeed, the basic approach for investigating the occurrence of PE consists in adding simple and labile organic molecules into a ambient sample containing the recalcitrant DOM pool. However, although this process remains microbially driven (Farjalla et al 2009;Guenet et al 2010), the role of microbial communities and their potential interaction are rarely taken into consideration (Bengtsson et al 2018). Yet, recent studies have shown that the metabolic fate of DOM could shift between catabolism and anabolism depending on nutrient loadings (Guillemette and del Giorgio 2012) and/or on the relative contribution of terrestrial DOM versus algal DOM (Guillemette et al 2016).…”
Section: * Thibault Lambertmentioning
confidence: 99%